A GEP-ISFG collaborative study on the optimization of an X-STR decaplex: data on 15 Iberian and Latin American populations - Gusmao, Leonor; Sanchez-Diz, Paula; Alves, Cintia; Gomes, Iva; Teresa Zarrabeitia, Maria; Abovich, Mariel; Atmetlla, Ivannia; Bobillo, Cecilia; Bravo, Luisa; Builes, Juan; Caine, Laura; Calvo, Raquel; et al. (Springer, 2009)
In a collaborative work carried out by the Spanish and Portuguese ISFG Working Group (GEP-ISFG), a polymerase chain reaction multiplex was optimized in order to type ten X-chromosome short tandem repeats (STRs) in a single reaction, including: DXS8378, DXS9902, DXS7132, DXS9898, DXS6809, DXS6789, DXS7133, GATA172D05, GATA31E08, and DXS7423. Using this X-decaplex, each 17 of the participating laboratories typed a population sample of approximately 200 unrelated individuals (100 males and 100 females). In this work, we report the allele frequencies for the ten X-STRs in 15 samples from Argentina (Buenos Aires, CA(3)rdoba, Rio Negro, Entre Rios, and Misiones), Brazil (SA o pound Paulo, Rio de Janeiro, Parana, and Mato Grosso do Sul), Colombia (Antioquia), Costa Rica, Portugal (Northern and Central regions), and Spain (Galicia and Cantabria). Gene diversities were calculated for the ten markers in each population and all values were above 56%. The average diversity per locus varied between 66%, for DXS7133, and 82%, for DXS6809. For this set of STRs, a high discrimination power was obtained in all populations, both in males (a parts per thousand yen1 in 5 A- 10(5)) and females (a parts per thousand yen1 in 3 A- 10(9)), as well as high mean exclusion chance in father/daughter duos (a parts per thousand yen99.953%) and in father/mother/daughter trios (a parts per thousand yen99.999%). Genetic distance analysis showed no significant differences between northern and central Portugal or between the two Spanish samples from Galicia and Cantabria. Inside Brazil, significant differences were found between Rio de Janeiro and the other three populations, as well as between SA o pound Paulo and Parana. For the five Argentinean samples, significant distances were only observed when comparing Misiones with Entre Rios and with Rio Negro, the only two samples that do not differ significantly from Costa Rica. Antioquia differed from all other samples, except the one from Rio Negro.
Keywords: X-chromosome; STRs; GEP-ISFG; Iberia; Latin America